IDEOLOGI KAPITALIS DAN MARXIS SERTA PENGARUHNYA TERHADAP KEHIDUPAN MASYARAKAT JEPANG DALAM NOVEL KANI KOUSEN KARYA KOBAYASHI TAKIJI - Ni wayan, Rianthi Agustini (Humanis; Volume 12. No.2. Agustus 2015, 2015)
Modernization that occurred in Japan in the Taishou era bring various influences to society. One of the influence was make a new class in sosiety that call borjuis. The research destination is for understand the view of capitalim, marxism, also for know the influence of capitalism and marxism. This research using descriptive analysis and dialectical techniques as methods and techniques of data analysis. Also use sociological theory of literature by Karl Marx and Engel, capitalist theory and Marxist theory by Kalr Marx. The result of research on the capitalist and marxist ideology also the influence to society lives in Kani Kousen by Kobayashi Takiji. Based on the analysis, there are the exploitation of workers, and the dominance of the class that became two basic view of capitalist ideology, while there are three basic view of capitalist ideology that was alienation, use tennoism for capitalism, and class state. The influence of capitalism are exploitation and alienation. The change of worker mainset to unite against the capitalism, establish labor organizations and strike action. In Kani Kousen, there two contadiction ideology that was capitalism and marxism.
Keywords: marxism, capitalist, taishou era